2014
DOI: 10.1590/s1809-98232014000200014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi Chuan on the elderly balance: a semi-experimental study

Abstract: Aging impairs the functional capacity, possibly compromising the balance over the years. However, Tai Chi Chuan is a martial art that can provide balance improvements in elderly people. This study aimed to evaluate balance in elderly after three and six months of Tai Chi Chuan practicing. Participants were 27 individuals (62±4.4 years) who underwent Tai Chi Chuan training (one hour each) twice a week, for six months. Balance was assessed by the Timed Up and Go (TUG) test, Berg Balance Scale (BBS) and Romberg t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is a simple test in which the elderly respondents were asked to stand up from a chair (resting position), walk a distance of three meters and then return to the chair and sit again (with their backs on the backrest). The respondents were instructed to perform the task safely and as quickly as possible and their performances were analyzed by counting the time they needed to complete the test (Konig, et al, 2014). Before each test, a familiarization protocol was conducted so as to ensure safety and accurate results.…”
Section: Functional Gaitmentioning
confidence: 99%
“…It is a simple test in which the elderly respondents were asked to stand up from a chair (resting position), walk a distance of three meters and then return to the chair and sit again (with their backs on the backrest). The respondents were instructed to perform the task safely and as quickly as possible and their performances were analyzed by counting the time they needed to complete the test (Konig, et al, 2014). Before each test, a familiarization protocol was conducted so as to ensure safety and accurate results.…”
Section: Functional Gaitmentioning
confidence: 99%
“…The effect of Tai Chi on postural control has been confirmed in older adults [46] and people with postural control dysfunction caused by various diseases, such as Diabetes mellitus [47], Parkinson's disease [48], and Stroke [49]. Tai Chi can improve the Balance Confidence Scale scores of the elderly [50,51], increase 6MWD [43,52], and shorten the time of TUG [43,53] in people with chronic diseases. In addition, in the aging population, modified Chen-style Tai Chi was found to be more effective than 24-style Tai Chi in enhancing health-related parameters [54].…”
Section: Dynamic Postural Controlmentioning
confidence: 99%
“…In conclusion, the study showed that TC makes significant progress in balance and fear of falling in older adults. In another study [13] , the effect of TC exercise on balance in 27 older adults was studied. All participants received a 60minute intervention two times per week for six months.…”
Section: Literature Reviewmentioning
confidence: 99%